A nationwide cross-sectional study on the association of patient-level factors with financial anxiety in the context of chronic medical conditions - Abbas M. Hassan; Carrie K. Chu; Jun Liu; Rebekah Angove; Gabrielle Rocque; Kathleen D. Gallagher; Adeyiza O. Momoh; Nicole E. Caston; Courtney P. Williams; Stephanie Wheeler; Anaeze C. Offodile (Scientific Reports, 2023)
Abstract Patient-level characteristics associated with the prevalence and severity of financial anxiety have yet to be described. We conducted a cross-sectional analysis of survey data assessing financial anxiety in patients with chronic medical conditions in December 2020. 1771 patients (42.6% response rate) participated in the survey. Younger age (19–35 age compared to ≥ 75 age) (β, 5.86; 95% CI 2.10–9.63), male sex (β, − 1.9; 95% CI − 3.1 to − 0.73), Hispanic/Latino race/ethnicity (compared with White patients) (β, 2.55; 95% CI 0.39–4.71), household size ≥ 4 (compare with single household) (β, 4.54; 95% CI 2.44–6.64), household income of ≥ $96,000-$119,999 (compared with ≤ $23,999) (β, − 3.2; 95% CI − 6.3 to 0.04), single marital status (compared with married) (β, 2.18; 95% CI 0.65–3.71), unemployment (β, 2.07; 95% CI 0.39–3.74), high-school education (compared with advanced degrees) (β, 3.10; 95% CI 1.32–4.89), lack of insurance coverage (compared with private insurance) (β, 6.05; 95% CI 2.66–9.45), more comorbidities (≥ 3 comorbidities compared to none) (β, 2.95; 95% CI 1.00–4.90) were all independently associated with financial anxiety. Patients who are young, female, unmarried, and representing vulnerable sub-populations are at elevated risk for financial anxiety.